UNDERSTANDING DIFFERENTIAL USE OF IN-HOME SERVICES AND NURSING HOME CARE BY RACE AND DEMENTIA DIAGNOSIS. (11th November 2018) - Applebaum, B; Nelson, I
Abstract: There has been a long-standing debate about whether non-whites have lower utilization rates of formal long-term services and supports than whites. Some work has argued that use has differed for nursing home care but not for home care. Other studies have suggested that the utilization rate differences are minimal once accounting for access and availability variations. In this paper we present utilization data by region for nursing home residents and home and community-based waiver participants in the context of the overall older population in select regions of Ohio. An examination of data by race and diagnosis in the context of state and regional population profiles allows us to identify utilization differences and could provide some insights as to where and why such differences exist. The paper will discuss what these differences mean for both service providers and policy makers.